Integration-Based Method as an Alternative Way to Estimate Parameters in the IV Bolus Compartment Model - Diny Zulkarnaen; Fadilah Ilahi; Muhammad Syifa Irfani; Dani Suandi ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2024)
An alternative method of integration-based parameter estimation applied in pharmacokinetics problems is proposed here. The method, introduced by Holder and Rodrigo, is used to estimate the rate of drug elimination and distribution when it enters the body via intravenous bolus. The estimation results are then compared with the classical method, the least squares method for the one-compartment model, and the residual method for the two-compartment model. Graphical simulations of drug concentration versus time are also performed in this article to view not only the dynamics of drug delivery in the body, but also the comparisons between the approximate solutions and the arbitrarily generated data points. Comparisons are also presented when the data points take into account noise in the form of random values. Based on the estimation and simulation results, the integration-based method gives good results and even better than the classical method although when noise is applied to the data points.